Pengaruh Volume Perdagangan, Volatilitas Harga Saham, Profitabilitas dan Operating Cash Flow terhadap Return Saham Pada Sektor Energi Tahun 2024 - Aditya Wardana; Bintis Ti’anatud Diniati; Rizza Tiaratu; Erika Dwi Maretya Nur Utami; Wildan Fathul Faza (CV. ALIM'SPUBLISHING, 2026)
The stock market is a place to buy shares for profit. In Indonesia, energy stocks are highly unpredictable because global commodity prices change constantly. This study examines what affected energy stock returns in 2024, focusing on trading volume, price swings, company profits, and cash flow. Using financial reports and statistical analysis, all these factors were tested together and individually. The results show that combined, all these factors do affect stock returns. However, when looked at one by one, only the company's net profit truly matters to investors. On the other hand, busy trading, daily price swings, and cash flow have no impact at all. In fact, all the factors studied only account for 14% of stock return movements, while the remaining 86% is driven by other outside forces. In conclusion, for those looking to invest in energy stocks, the most important thing to watch is the company's ability to generate net profit, rather than just looking at how busy daily transactions are in the market.